Accelerated whole‐heart coronary MRA using motion‐corrected sensitivity encoding with three‐dimensional projection reconstruction. Issue 1 (16th January 2014) - Pang, Jianing; Sharif, Behzad; Arsanjani, Reza; Bi, Xiaoming; Fan, Zhaoyang; Yang, Qi; Li, Kuncheng; Berman, Daniel S.; Li, Debiao
<x xml:space="preserve">Abstract</x> Purpose To achieve whole‐heart coronary magnetic resonance angiography (MRA) with (1.0 mm)3 spatial resolution and 5 min of free‐breathing scan time. Methods We used an electrocardiograph‐gated, T2‐prepared and fat‐saturated balanced steady state free precession sequence with 3DPR trajectory for free‐breathing data acquisition with 100% gating efficiency. For image reconstruction, we used a self‐calibrating iterative SENSE scheme with integrated retrospective motion correction. We performed healthy volunteer study to compare the proposed method with motion‐corrected gridding at different retrospective undersampling levels on apparent signal‐to‐noise ratio (aSNR) and subjective coronary artery (CA) visualization scores. Results Compared with gridding, the proposed method significantly improved both image quality metrics for undersampled datasets with 6000, 8000, and 10, 000 projections. With as few as 10, 000 projections, the proposed method yielded good CA visualization scores (3.02 of 4) and aSNR values comparable to those with 20, 000 projections. Conclusion Using the proposed method, good image quality was observed for free breathing whole‐heart coronary MRA at (1.0 mm)3 resolution with an achievable scan time of 5 min. Magn Reson Med 73:284–291, 2015. © 2014 Wiley Periodicals, Inc.